2017
DOI: 10.1017/s1352465817000480
|View full text |Cite
|
Sign up to set email alerts
|

Low-Intensity Cognitive Behavioural Therapy-Based Music Group (CBT-Music) for the Treatment of Symptoms of Anxiety and Depression: A Feasibility Study

Abstract: A low-intensity CBT-based music group can be successfully administered to clients of community mental health services. There are indications of effectiveness in reducing disability, although there appears to be negligible effect on symptoms of anxiety and depression. This is the first report of a trial of a low-intensity CBT-based music group intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
3
0
11

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 14 publications
3
3
0
11
Order By: Relevance
“…Our finding supports that of Trimmer et al [88] who showed that music with CBT has a significant effect in regulating emotions in that it serves as a motivator and reinforcer to participants. All in all, music therapy with cognitive behavioral therapy alters the automatic perception of schooling adolescents in that it builds their self-esteem and lessen social phobia.…”
Section: Discussionsupporting
confidence: 92%
“…Our finding supports that of Trimmer et al [88] who showed that music with CBT has a significant effect in regulating emotions in that it serves as a motivator and reinforcer to participants. All in all, music therapy with cognitive behavioral therapy alters the automatic perception of schooling adolescents in that it builds their self-esteem and lessen social phobia.…”
Section: Discussionsupporting
confidence: 92%
“…Perhaps, the music component of the program stimulated the attention of the children due to the attachment children to music. Buttressing this finding are the findings of Yoosefi et al, [ 26 ] Trimmer et al, [ 9 ] Trimmer et al, [ 15 ] and Egenti et al [ 8 ]…”
Section: Discussionsupporting
confidence: 64%
“…Egenti et al [ 8 ] found that music-based cognitive-behavioral therapy had significant effect on the reduction of social anxiety among the treatment group. However, Trimmer et al [ 15 ] found that music-based CBT significantly reduced symptoms of anxiety among the participants. Buttressing the results of the present study are the findings of the studies conducted by Ugwuanyi et al, [ 21 ] Akagy, [ 27 ] Bradshaw and Slade, [ 28 ] Saunders, [ 29 ] Shni, [ 30 ] Britton and Moore, [ 31 ] Britton, [ 32 ] Goldin et al, [ 33 ] Guetin et al, [ 34 ] Hakvoort and Bogaerts, [ 35 ] Klein et al [ 36 ] and Melfsen et al [ 37 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(e.g.,Shagan et al, 2018;Macfarlane et al, 2019). Delivery of Care 7 was addressed by 12 studies (3.44%); e.g.,Trimmer et al (2018) examined whether integrating music with CBT group therapy increased effectiveness and retention Preyde et al (2017). investigated the feasibility and acceptability of group music therapy among youth in a hospital's Child and Adolescent Mental Health unit.…”
mentioning
confidence: 99%